The Impact of Self-confidence, Self-motivation and Competitive State Anxiety on attentional control in athletes in China - Junli LIU , Tianyuan LIU , Jinglan SUN , (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
The sportsman's intentional control in any sports is the essential element needed for survival in the competitive global sports industry. An individual’s positive characteristics are considered the foremost solution to intentional control in the sports. The present study examines the role of sportsman's characteristics, such as self-confidence and competitive state anxiety on attentional control in athletes of China’s sports complex. The investigation of the moderating impact of self-motivation among the nexus of self-confidence, competitive state anxiety and attentional control in athletes is also included in the present study's purpose. The data has been collected using questionnaires filled out by athletes in China and has been analyzed using the smart-PLS. The results revealed that sportsman's characteristics, such as self-confidence, cognitive anxiety, and somatic anxiety, positively associate with attentional control in athletes of China’s sports complex. The results also exposed that the self-motivation has a significant moderating role among the nexus of self-confidence, cognitive anxiety, somatic anxiety and attentional control in athletes in China’s sports industry. These outcomes provide policymakers guidelines that they should increase their focus on personal characteristics of sportsman such as self-confidence and competitive state anxiety that enhance the level of attentional control in athletes.